2018
DOI: 10.1007/s12011-018-1454-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urbanization on Trace Element Concentration and Symmetry of Woodlice (Armadillidium vulgare Latreille, 1804)

Abstract: Woodlice are top consumers of a three-trophic system (soil, leaf litter, woodlice), and they are closely related to pollutant absorbing surfaces such as soil, leaf litter, and organic matter. We studied the effects of urbanization on trace element concentrations and fluctuating asymmetry of Armadillidium vulgare (Crustacea: Isopoda) individuals in and around Debrecen city, Hungary. Along an urbanization gradient (urban, suburban, and rural areas), trace element concentrations (Ba, Cu, Fe, Mn, Pb, and Zn) of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Both higher (Peters et al 2001) and lower (Godet et al 2012) levels of FA were reported from contaminated sites compared to control sites. Papp et al (2018) found no difference along an urban-rural gradient. Exploring a different type of environmental stress, Vilisics et al (2005) reported higher asymmetry at a locality with dramatic changes in soil moisture conditions, than from a more stable habitat.…”
Section: Terrestrial Isopods In Citiesmentioning
confidence: 81%
See 1 more Smart Citation
“…Both higher (Peters et al 2001) and lower (Godet et al 2012) levels of FA were reported from contaminated sites compared to control sites. Papp et al (2018) found no difference along an urban-rural gradient. Exploring a different type of environmental stress, Vilisics et al (2005) reported higher asymmetry at a locality with dramatic changes in soil moisture conditions, than from a more stable habitat.…”
Section: Terrestrial Isopods In Citiesmentioning
confidence: 81%
“…Isopods were proposed to use as indicators of pollution levels in cities (Dallinger et al 1992, Komarnicki 2005) and even at global scale (Hopkin et al 1993). Recently Pedrini-Martha et al (2012) showed that isopods are good indicators of mercury (Hg) contamination, while Papp et al (2018) reported significant differences in Ba and Cu concentration of Armadillidiumvulgare individuals along an urbanization gradient. Heavy metal concentration in isopod and other invertebrate tissue can be significantly affected by sampling and sample preparation protocols, which is important to keep in mind when making between-city comparisons (Zödl and Wittmann 2003).…”
Section: Terrestrial Isopods In Citiesmentioning
confidence: 99%
“…Ghemari et al (2019) determined the competition of cadmium (Cd), lead (Pb), zinc (Zn) and copper (Cu) on their assimilation on the food consumption and the growth of the terrestrial isopod Porcellio laevis Latreille, 1804. The effects of urbanization on trace element concentrations (Ba, Cu, Fe, Mn, Pb, and Zn) and fluctuating asymmetry of A. vulgare individuals in and around Debrecen city, Hungary were evaluated by Papp et al (2019). The researchers found that urbanization had a notable effect on Cu and Ba accumulations by A. vulgare from soil and leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these findings, woodlouse conservation should be a priority to protect and maintain biogeochemical cycles. The significance of these arthropods as bioindicators of ecosystems health status has been already emphasized ( Paoletti and Hassall, 1999 ; Solomou et al, 2019 ), together with their ability to accumulate heavy metals in their hepatopancreas (midgut caeca) vesicles ( Hopkin and Martin, 1982 ; Papp et al, 2019 ). However, there is no certainty on the impact that this could have on their performance as detritivores, since this tissue also harbors microorganisms related with cellulose and lignin biodegradation ( Hobbelen et al, 2004 ; Dittmer et al, 2016 ; Supplementary Table 1 ).…”
Section: Terrestrial Arthropods As a Case Of Ecosystem Holobiontsmentioning
confidence: 99%